Reaction Kinetics of Levulinic Acid Synthesis from Glucose Using Bronsted Acid Catalyst - Meutia Ermina Toif; Muslikhin Hidayat; Rochmadi Rochmadi; Arief Budiman (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Glucose is one of the primary derivative products from lignocellulosic biomass, which is abundantly available. Glucose has excellent potential to be converted into valuable compounds such as ethanol, sorbitol, gluconic acid, and levulinic acid (LA). Levulinic acid is an exceptionally promising green platform chemical. It comprises two functional groups, ketone and carboxylate, acting as highly reactive electrophiles for a nucleophilic attack. Therefore, it has extensive applications, including fuel additives, raw materials for the pharmaceutical industry, and cosmetics. This study reports the reaction kinetics of LA synthesis from glucose catalyzed by hydrochloric acid (HCl), a Bronsted acid, that was carried out under a wide range of operating conditions; i.e. the temperature of 140–180 °C, catalyst concentration of 0.5–1.5 M, and initial glucose concentration of 0.1–0.5 M. The highest LA yield of 48.34 % was able to be obtained from an initial glucose concentration of 0.1 M and by using 1 M HCl at 180 °C. The experimental results show that the Bronsted acid-catalyzed reaction pathway consists of glucose decomposition to levoglucosan (LG), conversion of LG to 5-hydroxymethylfurfural (HMF), and rehydration of HMF to LA. The experimental data yields a good fitting by assuming a first-order reaction model. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).